Biodiversity of wild alfalfa pollinators and their temporal foraging characters in Hexi Corridor, Northwest China - Wang, Xiaojuan; Liu, Hongping; Huang, Lichun; Zhang, Shuzhen; Deng, Zhigang; Li, Jing; Jin, Liang (Entomologica Fennica, 2012)
Seed production of alfalfa (Medicago sativa L.) is important in determining the effective distribution of new cultivars to farmers. However, little is known about the biodiversity and their community function of native wild pollinators of alfalfa in agronomic systems. We investigated the biodiversity of insects which visited alfalfa flowers and their temporal foraging characters in Hexi Corridor, China. A high biodiversity of insect visitors was discovered, 20 insect taxa in all, including 13 species of Hymenoptera, 3 species of Coleoptera, 3 species of Lepidoptera and 1 species of Diptera. Three native bee species, Andrena squamata, Anthophora melanognatha and Megachile abluta,were validated as the principal pollinators. They showed significant variations in tripping mode and their diurnal distribution patterns. Our results indicated that the native wild bees are diverse and they complement each other. This means they have developed a more complex system for the pollination of alfalfa than has been previously found out.